2013
DOI: 10.1111/cob.12028
|View full text |Cite
|
Sign up to set email alerts
|

Behaviours associated with weight loss maintenance and regaining in a Mediterranean population sample. A qualitative study

Abstract: The Mediterranean lifestyle has not been studied relative to weight loss maintenance. This study focused on a sample of Greek maintainers and regainers. Maintainers emphasized home-cooked meals; their diet does not appear to be low-fat, as home-cooked Greek meals are rich in olive oil. Having a small dinner is a common strategy among maintainers. Health motives were not mentioned by maintainers. Maintainers, but not regainers, appeared to compensate for emotional eating. Weight loss maintenance is imperative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 33 publications
2
47
1
Order By: Relevance
“…Note, those enrolled in the NWCR are not representative of all individuals who have attempted weight loss and who have experienced long-term maintenance, but rather are self-selected based on their success. Nevertheless, some findings from the NWCR are supported by those from the MedWeight registry in Greece, which includes both weight loss maintainers and regainers [82,83,84,85,86]. Among male registrants, weight loss maintainers were found to exhibit greater physical activity (approximately 200 kcal/day more than regainers), greater adherence to a dietary pattern emphasizing home-cooked meals, fruits, vegetables, unprocessed grains, nuts, lean proteins, low-fat dairy products, and olive oil, and lower daily intakes of salty snacks, sugary soda beverages, and alcohol.…”
Section: Can the Weight Loss-induced Energy Gap Be Attenuated By Lmentioning
confidence: 82%
“…Note, those enrolled in the NWCR are not representative of all individuals who have attempted weight loss and who have experienced long-term maintenance, but rather are self-selected based on their success. Nevertheless, some findings from the NWCR are supported by those from the MedWeight registry in Greece, which includes both weight loss maintainers and regainers [82,83,84,85,86]. Among male registrants, weight loss maintainers were found to exhibit greater physical activity (approximately 200 kcal/day more than regainers), greater adherence to a dietary pattern emphasizing home-cooked meals, fruits, vegetables, unprocessed grains, nuts, lean proteins, low-fat dairy products, and olive oil, and lower daily intakes of salty snacks, sugary soda beverages, and alcohol.…”
Section: Can the Weight Loss-induced Energy Gap Be Attenuated By Lmentioning
confidence: 82%
“…Along the same lines, a participant who successfully maintained weight loss after repeated attempts stated that they had tried many “diets” in the past, but were only successful when they decided, “no more diets, develop a healthy eating pattern” (Klingemann et al., ). Participants reframed dieting from a fixed‐term effort to a “long‐term venture”, accepting the “permanence” of the behavior changes required (Hindle & Carpenter, ; Karfopoulou, Mouliou, Koutras, & Yannakoulia, ).…”
Section: Resultsmentioning
confidence: 99%
“…And I think this was why I thought I've got to be more relaxed about it.” A second participant from the same study explained, “I went with the belief that this wasn't a diet, but what I'd got to do was change my way of eating” (Hindle & Carpenter, ). In a Greek study of weight loss maintainers following a Mediterranean diet, a participant explained, “… to realise that the X diet plan they will give you has to be a way of life, and not a 6‐month period you're following it and then going back, to how you were before” (Karfopoulou et al., ). In another British study of weight loss maintenance, a participant elaborated on this concept by couching diet as a temporary term: “I mean people say they are on a diet when they are a member of a slimming club sometimes but I don't think that's what you're on, you don't ever intend to go back to what you were doing before so that is not a diet you have just changed the way you eat now… I think you've got to tell yourself you're not on a diet you're just changing your way of life … you're not on a diet which is a temporary thing—you've got to educate yourself to eat differently all the time” (McKee et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Those who eat more earlier in the day lost significantly more weight (−8.2 vs −6.5 kg, p=.028), reduced waist circumference by more (−7 v −5 cm, p=.033), lost more fat mass (−6.8 vs −4.5 kg, p=.031) and improved their insulin sensitivity more. A qualitative study found that one strategy employed by individuals who maintained 10% weight loss for at least one year was eating small dinner, a strategy not employed by individuals who regained weight after an initial loss [72]. Finally, since glucose tolerance is known to be worse in the evening [73], late eating may also affect glycemic control in patients with diabetes.…”
Section: Potential Mediators Linking Evening Chronotype or Shiftwork mentioning
confidence: 99%